A schedule‐based medium access control protocol for mobile wireless sensor networks1. Issue 6 (15th March 2012) - Ngo, Vincent; Woungang, Isaac; Anpalagan, Alagan
ABSTRACT Recent advances in body area network technologies such as radio frequency identification and ham radio, to name a few, have introduced a huge gap between the use of current wireless sensor network technologies and specific needs of some important wireless sensor network applications such as medical care, disaster relief, or emergency preparedness and response. In these types of applications, the mobility of nodes can occur, leading to the challenge of mobility handling. In this paper, we address this challenge by prioritizing transmissions of mobile nodes over static nodes. This is achieved by using shorter contention windows in reservation slots for mobile nodes (the so‐called backoff technique) combined with a novel hybrid medium access control (MAC) protocol (the so‐called versatile MAC). The proposed protocol advocates channel reuse for bandwidth efficiency and management purpose. Through extensive simulations, our protocol is compared with other MAC alternatives such as time division multiple access and IEEE 802.11 with request to send/clear to send exchange, chosen as benchmarks. The performance metrics used are bandwidth utilization, fairness of medium access, and energy consumption. The superiority of versatile MAC against the studied benchmark protocols is established with respect to these metrics. Copyright © 2012 John Wiley & Sons, Ltd.